Analisis Socio-Legal terhadap Penanggulangan Pertambangan Timah Ilegal di Provinsi Kepulauan Bangka Belitung - Yang Meliana; Eko Riyadi (Jurnal Hukum Lex Generalis, 2026)
Unlicensed tin extraction activities in the Bangka Belitung Islands Province have generated widespread social, economic, and ecological consequences. The present study seeks to examine the efforts undertaken to address illegal tin mining by employing a socio-legal framework. The study adopts an empirical legal methodology grounded in a socio-legal perspective. Findings reveal that efforts to curb illegal mining have remained suboptimal, attributable to inadequate oversight mechanisms, the heavy economic reliance of local communities on the tin industry, and the absence of coherent alignment between penal and non-penal regulatory frameworks. Accordingly, the formulation of an evidence-based criminal policy that cohesively brings together law enforcement, regulatory oversight, and community empowerment is urgently needed.